Studies on Different Levels of Fertigation on Fruit Attributes and Quality of Pomegranate (Punica granatum L.) cv. Super Bhagwa - Jadhav, A. R.; Dheware, R. M.; Shinde, M. K. (International Journal of Bio-resource and Stress Management, 2023)
The experiment was conducted at Gangapur, Latur, Maharashtra, India during (Dec, 2017–June, 2018) to study effective use of fertilizers with a goal to match nutrient supply with crop requirements and minimize nutrient losses from fields. Fertilizers are considered basic requirements to get the maximum yield, quality and productivity of trees. Fertigation is advantageous over the application of solid fertilizers in the soil by minimizing the losses of fertilizers through runoff and leaching and increase the nutrient-use efficiency and saving amount of fertilizers, therefore to study the different levels of fertigation (Surface irrigation+RDF-control; Drip irrigation+RDF; 50% RDF through fertigation; 75% RDF through fertigation; 100% RDF through fertigation and 125% RDF through fertigation) on fruit attributes and quality of pomegranate (Punica granatum L.) cv. Super Bhagwa. The experiment was laid out in a Randomized Block Design with six treatments and four replications. The investigation indicated 75% recommended dose of fertilizers through fertigation resulted, the highest average fruit weight (258.65 g), fruit volume (225.50 ml), weight of hundred arils (35.47 g), rind thickness (4.97 mm), rind weight (113.92 g) and arils weight (144.73 g). Same treatment recorded maximum juice percentage (80.20%), reducing sugar (11.70%), total sugar (12.83%) and T.S.S.: Acid ratio (45.60). Therefore, 75% recommended dose of fertilizers through fertigation can be recommended for improve fruit attributes and quality of pomegranate cv. Super Bhagwa for four to five years old tree.